Comparative efficacy of mineral trioxide aggregate and biodentine for the repair of pulpal floor perforation (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
In the present study, the clinical outcome of mineral trioxide aggregate and Biodentine as repairing materials in the management of pulpal floor perforation was compared in vivo. Thirty teeth having pulpal floor perforation were enrolled in this study, out of which 15 perforations were repaired with mineral trioxide aggregate and the remaining 15 were subjected to Biodentine treatment. Following perforation repair, each tooth was then subjected to root canal therapy. Patients were recalled at 3, 6 and 12 month interval. The assessment of pain, pain on palpation, tenderness on percussion, and radiological evaluation was performed to determine the repair ability of pulpal floor perforation. Statistical analysis was performed with Chi-square test between the two groups and a value of p